Ion Exchange Technologies - Kilislioğlu, Ayben (IntechOpen, 2012)
This book contains information about the technological development of ion exchange in their application for industrial processes. Widely used and well known fields of ion exchange like chromatography and electromembrane technology are described in this book with experimental details. Designing new materials for nanotechnology and nanomaterials as ion exchanger are also explained by experimental proofs. Ion exchange book is suitable not only for postgraduate students but also for researchers in chemistry, biochemistry and chemical technology.